Battery tab and preparation method thereof
By combining highly conductive copper materials with composite functional materials and adhesives in the battery electrode ear, specific process steps are adopted to solve the problems of reduced conductivity and insufficient material stability in the battery electrode ear in high temperature environment, and higher conductivity, corrosion resistance and thermal stability are achieved.
Patent Information
- Application Number
- CN202411640828.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The conductivity of existing battery ears has decreased during long-term use, especially in high-temperature environments. Inadequate material stability leads to deterioration. At the same time, the bond strength and dispersion of the reinforced material and metal materials are poor, affecting structural stability and corrosion resistance.
Highly conductive copper materials are used to combine them with composite functional materials and adhesives, including yttrium oxide-doped cerium, boron nitride nanosheets, rare element rhenium and aluminosilicate adhesives. Through process steps such as drying, ball milling, step-by-step sintering and controlled cooling annealing, the uniform distribution and stable bonding of the materials are ensured.
It improves the conductivity, corrosion resistance and thermal stability of the battery ears, extends the service life, especially in high temperature and high humidity environments, and reduces contact resistance and energy loss.
Smart Images

Figure BDA0005138386860000081 
Figure BDA0005138386860000082 
Figure BDA0005138386860000083
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a battery tab and a preparation method thereof. Background Art
[0002] In the prior art, battery tabs usually use highly conductive metal materials to ensure conductivity, and are supplemented with reinforcing materials to improve structural strength and thermal stability. Commonly used conductive materials include copper, aluminum, etc., which are usually used in combination with other composite materials to meet the stringent requirements of batteries under high power output and high temperature conditions. At the same time, some conductive reinforcing materials and nanomaterials are used to improve the durability and electrical properties of battery tabs, thereby improving the overall efficiency of the battery.
[0003] However, there are still some technical problems in the existing battery tab design. First, the battery tab may face a decrease in conductivity during long-term use, especially in high-temperature environments, where insufficient material stability may lead to performance degradation. Second, the existing reinforcement materials have poor bonding strength and dispersion with metal materials, which may affect the overall structural stability and corrosion resistance of the tab.
[0004] Therefore, it is necessary to develop an improved battery tab. Summary of the invention
[0005] The present application provides a battery tab and a preparation method thereof, as well as the mechanical strength and electrical conductivity of the battery tab.
[0006] The present application provides a battery tab, the battery tab comprising a highly conductive metal material, a composite functional material and an adhesive, the composite functional material comprising an inorganic conductive reinforcing material, a nano-reinforcing material and a rare element dopant;
[0007] The highly conductive metal material is copper, accounting for 80% of the mass of the battery tab;
[0008] The inorganic conductive reinforcing material is yttrium oxide doped with cerium, wherein the content of cerium in the yttrium oxide doped with cerium is 1% of the total mass of yttrium oxide; the mass ratio of the yttrium oxide doped with cerium to the battery tab is 10%;
[0009] The nano-enhanced material is boron nitride nanosheets, and the mass ratio of the boron nitride nanosheets to the battery tab is 3%;
[0010] The rare element dopant is rhenium, and the mass ratio of the rare element dopant to the battery tab is 0.5%;
[0011] The adhesive is aluminosilicate adhesive, accounting for 6.5% of the mass of the battery tab.
[0012] Furthermore, the particle size of the boron nitride nanosheets is 100 nanometers.
[0013] Furthermore, the boron nitride nanosheets are hexagonal crystals.
[0014] Furthermore, the copper is spherical copper powder.
[0015] The present application provides a method for preparing a battery tab, comprising:
[0016] The material pretreatment step S101 specifically includes: drying the component materials, wherein the copper powder is dried in a vacuum environment at 120 degrees Celsius for 2 hours to remove moisture and impurities; the yttrium oxide doped cerium and boron nitride nanosheets are dried in a nitrogen atmosphere at 200 degrees Celsius for 3 hours respectively to enhance the surface activity; the rhenium particles and the aluminosilicate adhesive are dried in an environment at 150 degrees Celsius for 2 hours to ensure the stability of all materials;
[0017] The material mixing and ball milling step S102 specifically comprises: uniformly mixing the materials according to the following mass ratios: 80% copper, 10% yttrium oxide doped cerium, 3% boron nitride, 0.5% rhenium, and 6.5% aluminosilicate adhesive; wherein the cerium content in the yttrium oxide doped cerium is 1% of the total mass of the yttrium oxide; adding the mixture into a ball mill under argon protection, and ball milling for 6 hours at a speed of 300 revolutions per minute, using silicon nitride balls as grinding media, to ensure that the yttrium oxide doped cerium, boron nitride nanosheets, and rhenium particles are uniformly distributed around the copper powder and the aluminosilicate adhesive, so as to obtain a uniform mixture;
[0018] The step-by-step sintering step S103 specifically includes sequentially performing the following step-by-step sintering treatments on the ball-milled mixed powder in a nitrogen protection environment:
[0019] Low-temperature pre-sintering: The mixed powder is heated to 650 degrees Celsius and maintained for 1 hour to remove stress in the material and enhance the initial bonding between the components;
[0020] High temperature sintering: The pre-sintered material is heated to 1000 degrees Celsius and maintained for 3 hours to promote a strong chemical bond between the copper powder and the yttrium-doped cerium oxide, boron nitride and aluminosilicate adhesive, thereby improving the overall structural strength and conductivity;
[0021] Controlled cooling annealing: The high-temperature sintered material is cooled to 200 degrees Celsius and annealed at this temperature for 1 hour to eliminate the thermal stress during the sintering process and further improve the conductivity and corrosion resistance of the material;
[0022] Cooling and post-processing step S104: slowly cooling the annealed material to room temperature in a nitrogen environment to ensure structural stability; polishing the material surface after cooling to ensure surface smoothness, thereby reducing contact resistance.
[0023] The battery tabs of the present invention have excellent electrical conductivity and durability through unique formula and process optimization. In actual use environment, the copper matrix provides a basic conductive skeleton, and yttrium oxide doped cerium further improves the electrical conductivity and corrosion resistance of the material. The addition of boron nitride nanosheets forms a stable thermal conductive network structure, which improves the overall thermal conductivity and mechanical strength. Rhenium as a rare element dopant provides better interface stability and antioxidant properties, ensuring the long-term reliability of the material in high temperature and complex environments. In addition, the use of aluminosilicate adhesives significantly improves the overall bonding strength of the material and extends the service life of the battery tabs.
[0024] Compared with the prior art, the technical effect of the present invention is positive and obvious. The composite functional battery tab provided by the present invention improves the conductivity, corrosion resistance and thermal stability of the tab by optimizing the formula and preparation process, thereby improving the reliability of the battery in various use environments, reducing contact resistance, reducing energy loss, and ensuring the safety and stability of the battery during long-term use. Especially in high temperature and high humidity environments, the battery tab of the present invention shows excellent performance stability, and the resistance change rate is significantly lower than that of the prior art solution, which is of great significance to improving the overall performance of the battery. DETAILED DESCRIPTION
[0025] Many specific details are described in the following description to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways than those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present application, so the present application is not limited by the specific implementation disclosed below.
[0026] Example 1
[0027] Embodiment 1 provides a battery tab, the battery tab comprising a highly conductive metal material, a composite functional material and an adhesive, the composite functional material comprising an inorganic conductive reinforcing material, a nano-reinforcing material and a rare element dopant;
[0028] The highly conductive metal material is copper, accounting for 80% of the mass of the battery tab;
[0029] The inorganic conductive reinforcing material is yttrium oxide doped with cerium, wherein the content of cerium in the yttrium oxide doped with cerium is 1% of the total mass of yttrium oxide; the mass ratio of the yttrium oxide doped with cerium to the battery tab is 10%;
[0030] The nano-enhanced material is boron nitride nanosheets, and the mass ratio of the boron nitride nanosheets to the battery tab is 3%;
[0031] The rare element dopant is rhenium, and the mass ratio of the rare element dopant to the battery tab is 0.5%;
[0032] The adhesive is aluminosilicate adhesive, accounting for 6.5% of the mass of the battery tab.
[0033] Wherein, the particle size of the boron nitride nanosheets is 100 nanometers.
[0034] Wherein, the boron nitride nanosheets are hexagonal crystals.
[0035] Wherein, the copper is spherical copper powder.
[0036] In this embodiment 1, a detailed preparation method of a battery tab is provided to ensure that the battery tab can achieve expected performance in terms of high conductivity and structural stability. The battery tab is composed of a highly conductive metal material, a composite functional material and an adhesive.
[0037] First, the highly conductive metal material is copper, and spherical copper powder is selected. Its particle structure and spherical shape can optimize the dispersion and close arrangement of the material while ensuring conductivity. The copper powder accounts for 80% of the total mass of the battery tab.
[0038] The components of the composite functional material include inorganic conductive reinforcement materials, nano-reinforcement materials and rare element dopants. Among them, the inorganic conductive reinforcement material uses yttrium oxide doped cerium, accounting for 10% of the total mass of the battery tab, to enhance the conductivity and high temperature resistance of the tab material. Specifically, the mass proportion of cerium in yttrium oxide doped cerium is controlled to 1% of the total mass of yttrium oxide. This doping method can effectively improve the conductivity and chemical stability of the material, and at the same time improve the structural integrity of the material in a high temperature environment through the action of yttrium oxide.
[0039] The nano-reinforcement material is boron nitride nanosheets, which account for 3% of the total mass of the battery tab. The reason for selecting boron nitride nanosheets is that they have excellent mechanical strength and thermal conductivity, which contribute to the durability and heat dissipation effect of the battery tabs during the charge and discharge cycle. In addition, these boron nitride nanosheets have a hexagonal structure, and the particle size is controlled to be around 100 nanometers. This morphology and particle size optimize the distribution and reinforcement effect of boron nitride in the composite material. The hexagonal boron nitride structure helps to provide additional mechanical support, so that the entire battery tab can still remain stable under high temperature and mechanical stress. In this embodiment, the boron nitride with a specification of 100nm produced by Shanghai Yaotian New Materials Technology Co., Ltd. is selected.
[0040] Rhenium is selected as a rare element dopant, accounting for 0.5% of the mass ratio of the battery tab. As a rare element, although the amount of rhenium added is small, it can significantly improve the conductivity and corrosion resistance of the composite material. The micro-refining of rhenium particles ensures its uniform distribution in the battery tab, thereby improving the conductivity of the composite material without affecting the structural integrity.
[0041] The adhesive is selected from aluminosilicate adhesive, which accounts for 6.5% of the mass ratio of the battery tab. Aluminosilicate adhesive has high temperature resistance and chemical stability, which can ensure that the structure of the bonding material of the battery tab is not damaged in a high temperature environment, while providing sufficient bonding strength to maintain the combination of various material components. In this embodiment, the aluminosilicate adhesive can be a high-temperature resistant aluminosilicate-based adhesive, which has the characteristic of maintaining bonding strength at temperatures above 1000°C. Preferably, aluminosilicate adhesive products commonly used on the market can be selected, such as HR-8767C high-temperature adhesive produced by Dongguan Huirui Adhesive Co., Ltd., which is composed of aluminosilicate.
[0042] Example 2
[0043] Embodiment 2 provides a method for preparing a battery tab, comprising:
[0044] The material pretreatment step S101 specifically includes: drying the component materials, wherein the copper powder is dried in a vacuum environment at 120 degrees Celsius for 2 hours to remove moisture and impurities; the yttrium oxide doped cerium and boron nitride nanosheets are dried in a nitrogen atmosphere at 200 degrees Celsius for 3 hours respectively to enhance the surface activity; the rhenium particles and the aluminosilicate adhesive are dried in an environment at 150 degrees Celsius for 2 hours to ensure the stability of all materials;
[0045] The material mixing and ball milling step S102 specifically comprises: uniformly mixing the materials according to the following mass ratios: 80% copper, 10% yttrium oxide doped cerium, 3% boron nitride, 0.5% rhenium, and 6.5% aluminosilicate adhesive; wherein the cerium content in the yttrium oxide doped cerium is 1% of the total mass of the yttrium oxide; adding the mixture into a ball mill under argon protection, and ball milling for 6 hours at a speed of 300 revolutions per minute, using silicon nitride balls as grinding media, to ensure that the yttrium oxide doped cerium, boron nitride nanosheets, and rhenium particles are uniformly distributed around the copper powder and the aluminosilicate adhesive, so as to obtain a uniform mixture;
[0046] The step-by-step sintering step S103 specifically includes sequentially performing the following step-by-step sintering treatments on the ball-milled mixed powder in a nitrogen protection environment:
[0047] Low-temperature pre-sintering: The mixed powder is heated to 650 degrees Celsius and maintained for 1 hour to remove stress in the material and enhance the initial bonding between the components;
[0048] High temperature sintering: The pre-sintered material is heated to 1000 degrees Celsius and maintained for 3 hours to promote a strong chemical bond between the copper powder and the yttrium-doped cerium oxide, boron nitride and aluminosilicate adhesive, thereby improving the overall structural strength and conductivity;
[0049] Controlled cooling annealing: The high-temperature sintered material is cooled to 200 degrees Celsius and annealed at this temperature for 1 hour to eliminate the thermal stress during the sintering process and further improve the conductivity and corrosion resistance of the material;
[0050] Cooling and post-processing step S104: slowly cooling the annealed material to room temperature in a nitrogen environment to ensure structural stability; polishing the material surface after cooling to ensure surface smoothness, thereby reducing contact resistance.
[0051] Wherein, the particle size of the boron nitride nanosheets is 100 nanometers.
[0052] Wherein, the boron nitride nanosheets are hexagonal crystals.
[0053] Wherein, the copper is spherical copper powder.
[0054] In this embodiment 2, a detailed preparation method of a battery tab is provided to ensure that the prepared battery tab can achieve ideal performance in terms of conductivity and mechanical strength. The entire preparation method includes material pretreatment, mixed ball milling, step-by-step sintering, and final cooling and surface treatment steps. The temperature, time, and environmental control in each step are precisely designed to ensure the maximization of material properties and the stability of the material during the preparation process.
[0055] First, in the material pretreatment step, each component material is dried independently to remove moisture and impurities and enhance the activity of the material surface. Spherical particles are selected for copper powder to ensure uniform dispersion and good conductivity in subsequent processes. The copper powder is placed in a vacuum environment at 120 degrees Celsius and dried for 2 hours to fully remove moisture and impurities therein. The drying treatment of yttrium oxide doped cerium and boron nitride nanosheets adopts a nitrogen atmosphere of 200 degrees Celsius and is dried for 3 hours respectively to avoid oxidation and enhance the surface activity of the material. The use of a nitrogen atmosphere helps to protect the chemical properties of the material. For rhenium particles and aluminosilicate adhesives, they are dried in an environment of 150 degrees Celsius for 2 hours to ensure the stability of these materials and avoid decomposition or property changes in a high temperature environment. In this embodiment, the aluminosilicate adhesive can be a high temperature resistant aluminosilicate-based adhesive, which has the characteristic of maintaining bonding strength at temperatures above 1000°C. Preferably, a common aluminosilicate adhesive product on the market can be selected, such as HR-8767C high temperature adhesive produced by Dongguan Huirui Adhesive Co., Ltd., which contains aluminosilicate.
[0056] After the pretreatment is completed, the material mixing and ball milling step is entered. In this step, each component material is accurately weighed according to the mass ratio, and 80% copper, 10% yttrium oxide doped cerium, 3% boron nitride, 0.5% rhenium and 6.5% aluminosilicate adhesive are added to the mixer in sequence. In particular, the cerium content in yttrium oxide doped cerium is controlled to 1% of the total mass of yttrium oxide to ensure the conductive enhancement effect of the composite material. Under argon protection, the mixture is added to a ball mill to avoid oxidation of copper, and ball milling is performed for 6 hours at a speed of 300 revolutions per minute. Silicon nitride balls are used as grinding media to ensure that yttrium oxide doped cerium, boron nitride nanosheets and rhenium particles can be evenly distributed around copper powder and aluminosilicate adhesive, thereby obtaining a uniform mixture. In this embodiment, boron nitride with a specification of 100nm produced by Shanghai Yaotian New Materials Technology Co., Ltd. is selected.
[0057] Next, a step-by-step sintering step is carried out to ensure the firm bonding of the materials and improve their structural strength. First, a low-temperature pre-sintering is carried out, and the ball-milled mixed powder is heated to 650 degrees Celsius and kept for 1 hour. This process helps to remove residual stress in the material and enhance the initial bonding between the components to form a stable composite structure. After that, a high-temperature sintering is carried out, and the pre-sintered material is heated to 1000 degrees Celsius and kept for 3 hours to ensure a firm chemical bond between the copper powder, yttrium oxide-doped cerium, boron nitride and aluminosilicate adhesive, thereby improving the overall structural strength and conductivity. The high-temperature sintering process enables a closer bond between the material components and improves the conductive properties of the composite material.
[0058] After sintering, controlled cooling annealing is performed to eliminate the thermal stress generated during the sintering process. Specifically, the material after high-temperature sintering is slowly cooled to 200 degrees Celsius and annealed at this temperature for 1 hour. The controlled cooling annealing process helps to eliminate internal thermal stress, making the material structure more stable, while further improving conductivity and corrosion resistance, thereby ensuring the durability and stability of the material in subsequent use.
[0059] Finally, in the cooling and post-processing step, the annealed material is slowly cooled to room temperature in a nitrogen environment to ensure the overall stability of the structure. After cooling, the surface of the material is polished to improve the surface finish and reduce the contact resistance, thereby improving the conductive properties of the material. Polishing can reduce the surface roughness, optimize the contact effect of the battery tab, and provide excellent conductivity for the final application.
[0060] During the entire process, the particle size of boron nitride nanosheets is controlled at 100 nanometers, and boron nitride has a hexagonal crystal structure, which further enhances the mechanical properties and thermal conductivity of the composite material.
[0061] Comparative Example 1 (ordinary rolled copper foil tab):
[0062] The raw material is T2 copper with a purity of ≥99.9%. The specific preparation steps are as follows: the cast copper ingot is subjected to rough rolling, the temperature is controlled at 150-200℃, the rolling ratio is 15:1, and a copper strip with a thickness of about 2mm is obtained; the rough-rolled copper strip is annealed at a temperature of 650℃ for 30 minutes to eliminate processing stress; multiple passes of fine rolling are performed, and the deformation of each pass is controlled between 20%-30%, and finally rolled to a thickness of 0.2mm; after online tension straightening, the tension is controlled between 80-120N; the surface of the copper foil is polished with a 1000 mesh diamond polishing wheel to make the surface roughness Ra≤0.4μm; finally, slitting is performed and precision cutting is performed according to the design size of the pole ear.
[0063] Comparative Example 2 (nickel-plated copper foil tab):
[0064] The substrate is the 0.2 mm copper foil prepared in Comparative Example 1. The specific nickel plating steps are as follows:
[0065] (1) Surface pretreatment:
[0066] Alkali degreasing: use 40g / L sodium hydroxide solution, temperature 60℃, soak for 3 minutes; water washing: rinse with deionized water twice, 1 minute each time; acid pickling activation: 10% sulfuric acid solution, soak for 1 minute at room temperature; water washing: rinse with deionized water twice, 1 minute each time.
[0067] (2) Nickel plating process:
[0068] Plating solution composition: Nickel sulfate: 250g / L Nickel chloride: 45g / L Boric acid: 40g / L
[0069] Process parameters: Temperature: 55±2℃ pH value: 4.0-4.5 Current density: 3-5A / dm 2 Plating time: 8-10 minutes Stirring speed: 150rpm
[0070] (3) Post-processing:
[0071] Washing: Rinse with deionized water 3 times, 1 minute each time
[0072] Drying: 80℃ oven drying for 10 minutes
[0073] Heat treatment: annealing at 200℃ for 15 minutes under nitrogen protection to improve the bonding strength of the coating
[0074] (4) Quality inspection:
[0075] Coating thickness: 2-3μm (detected by X-ray thickness gauge)
[0076] Adhesion: No peeling in tape peeling test
[0077] Surface appearance: bright and uniform, without spots, bubbles and other defects.
[0078] The following is a performance comparison table of the battery tabs prepared using Example 2 of the present application and the battery tabs of Comparative Examples 1 and 2.
[0079] Table 1. Comparison of basic physical properties of battery tabs
[0080]
[0081] Table 2. Electrical performance test results
[0082]
[0083] Table 3. Mechanical properties test results
[0084]
[0085] Table 4. Durability test results
[0086]
[0087] In order to verify the performance advantages of the battery tabs of the present invention, two mainstream battery tab products in the current market were selected for comparison: Comparative Example 1 was prepared using a common rolled copper foil process, and Comparative Example 2 was prepared using a nickel-plated copper foil process. Through the performance test of the system, the following results were obtained:
[0088] First of all, from the basic physical properties (Table 1), the density of the three samples is close to the theoretical density of pure copper (8.96g / cm 3 ), among which Comparative Example 1 is closest to the theoretical value, which is due to its pure copper structure. The density of the battery ear sample provided in Example 2 is slightly lower, which is consistent with its composite structure characteristics. In terms of surface roughness, the battery ear sample provided in Example 2 reaches 0.30μm, which is better than Comparative Examples 1 and 2, mainly due to its unique material system and post-processing process. Although the battery ear provided in Example 2 has a slightly lower thickness control accuracy (±8μm), it is still within the acceptable range for practical applications. Although the thermal conductivity is slightly lower than that of the comparative sample, the level of 372W / m·K can meet the actual use requirements.
[0089] In terms of key electrical properties (Table 2), the battery lug sample provided in Example 2 exhibits excellent comprehensive performance. Its volume resistivity is 1.75μΩ·cm, which is between the two comparative examples, indicating that its basic conductive performance is good. It is particularly noteworthy that the contact resistance of the battery lug sample provided in Example 2 is only 0.58mΩ, which is lower than the two comparative examples, which is of great significance for improving the actual use efficiency of the battery. More importantly, after 168 hours in a high temperature environment of 85°C, the resistance change rate of the battery lug sample provided in Example 2 is only +6.8%, which is significantly better than +15.2% of Comparative Example 1 and +8.5% of Comparative Example 2, indicating that it has better high-temperature conductive stability.
[0090] The mechanical properties test results (Table 3) show that although the tensile strength (308MPa) of the battery lug sample provided in Example 2 is slightly lower than that of the comparative example, its elongation reaches 12%, which is significantly higher than 8% of comparative example 1 and 7% of comparative example 2. Higher elongation means better flexibility, which is crucial to the reliability of the battery during assembly and use. In the 180° bending test, the battery lug sample provided in Example 2 can withstand 20 bends, which is better than 15 times of comparative example 1 and 12 times of comparative example 2. At the same time, the peel strength of the battery lug sample provided in Example 2 reaches 15N / cm, which is higher than 12N / cm of comparative example 2, indicating that its interface bonding performance is better.
[0091] In the durability test (Table 4), the battery tab sample provided in Example 2 showed comprehensive advantages. After immersion in a 3.5% sodium chloride solution for 96 hours, the mass loss was only 0.04%, which is better than 0.12% of Comparative Example 1 and 0.05% of Comparative Example 2, indicating that it has excellent corrosion resistance. In the thermal cycle test from -40°C to 85°C, the resistance change rate after 100 cycles was +7.5%, which is significantly lower than +12.5% of Comparative Example 1 and +8.2% of Comparative Example 2. After 96 hours in a high temperature and high humidity (85°C / 85%RH) environment, the resistance change rate was only +8.8%, while Comparative Example 1 and Comparative Example 2 were +18.2% and +10.5%, respectively, proving the excellent environmental adaptability of the battery tab sample provided in Example 2.
[0092] In summary, although the battery tabs provided in Example 2 are slightly lower than existing products in some conventional indicators, they show obvious advantages in key performance indicators such as elongation, bending performance, corrosion resistance, and high temperature and high humidity stability, especially in terms of performance stability in harsh environments, which is of great significance to improving the reliability and service life of the battery.
[0093] Although the present application is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present application. Any technical personnel in this field may make possible changes and modifications without departing from the spirit and scope of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.
Claims
1. A battery tab, characterized in that: The battery tab comprises a highly conductive metal material, a composite functional material and an adhesive, wherein the composite functional material comprises an inorganic conductive reinforcing material, a nano-enhancing material and a rare element dopant; The highly conductive metal material is copper, accounting for 80% of the mass of the battery tab; The inorganic conductive reinforcing material is yttrium oxide doped with cerium, wherein the content of cerium in the yttrium oxide doped with cerium is 1% of the total mass of yttrium oxide; the mass ratio of the yttrium oxide doped with cerium to the battery tab is 10%; The nano-enhanced material is boron nitride nanosheets, and the mass ratio of the boron nitride nanosheets to the battery tab is 3%; The rare element dopant is rhenium, and the mass ratio of the rare element dopant to the battery tab is 0.5%; The adhesive is aluminosilicate adhesive, accounting for 6.5% of the mass of the battery tab.
2. The battery tab according to claim 1, characterized in that: The particle size of the boron nitride nanosheets is 100 nanometers.
3. The battery tab according to claim 1, characterized in that: The boron nitride nanosheets are hexagonal crystals.
4. The battery tab according to claim 1, characterized in that: The copper is spherical copper powder.
5. A method for preparing a battery tab, characterized in that: include: The material pretreatment step S101 specifically includes: drying the component materials, wherein the copper powder is dried in a vacuum environment at 120 degrees Celsius for 2 hours to remove moisture and impurities; the yttrium oxide doped cerium and boron nitride nanosheets are dried in a nitrogen atmosphere at 200 degrees Celsius for 3 hours respectively to enhance the surface activity; the rhenium particles and the aluminosilicate adhesive are dried in an environment at 150 degrees Celsius for 2 hours to ensure the stability of all materials; The material mixing and ball milling step S102 specifically comprises: uniformly mixing the materials according to the following mass ratios: 80% copper, 10% yttrium oxide doped cerium, 3% boron nitride, 0.5% rhenium, and 6.5% aluminosilicate adhesive; wherein the cerium content in the yttrium oxide doped cerium is 1% of the total mass of the yttrium oxide; adding the mixture into a ball mill under argon protection, and ball milling for 6 hours at a speed of 300 revolutions per minute, using silicon nitride balls as grinding media, to ensure that the yttrium oxide doped cerium, boron nitride nanosheets, and rhenium particles are uniformly distributed around the copper powder and the aluminosilicate adhesive, so as to obtain a uniform mixture; The step-by-step sintering step S103 specifically includes sequentially performing the following step-by-step sintering treatments on the ball-milled mixed powder under a nitrogen protection environment: Low-temperature pre-sintering: The mixed powder is heated to 650 degrees Celsius and maintained for 1 hour to remove stress in the material and enhance the initial bonding between the components; High temperature sintering: The pre-sintered material is heated to 1000 degrees Celsius and maintained for 3 hours to promote a strong chemical bond between the copper powder and the yttrium-doped cerium oxide, boron nitride and aluminosilicate adhesive, thereby improving the overall structural strength and conductivity; Controlled cooling annealing: The material after high-temperature sintering is cooled to 200 degrees Celsius and annealed at this temperature for 1 hour to eliminate the thermal stress during the sintering process and further improve the conductivity and corrosion resistance of the material; Cooling and post-processing step S104: slowly cooling the annealed material to room temperature in a nitrogen environment to ensure structural stability; polishing the material surface after cooling to ensure surface smoothness, thereby reducing contact resistance.